Nucleophilic Radiofluorination Using Tri-tert-Butanol Ammonium as a Bifunctional Organocatalyst: Mechanism and Energetics - Oh, Young-Ho; Shinde, Sandip S.; Lee, Sungyul (Molecules, 2022)
We present a quantum chemical analysis of the F-18-fluorination of 1,3-ditosylpropane, promoted by a quaternary ammonium salt (tri-(tert-butanol)-methylammonium iodide (TBMA-I) with moderate to good radiochemical yields (RCYs), experimentally observed by Shinde et al. We obtained the mechanism of the S(N)2 process, focusing on the role of the -OH functional groups facilitating the reactions. We found that the counter-cation TBMA(+) acts as a bifunctional promoter: the -OH groups function as a bidentate 'anchor' bridging the nucleophile [F-18]F- and the -OTs leaving group or the third -OH. These electrostatic interactions cooperate for the formation of the transition states of a very compact configuration for facile S(N)2 F-18-fluorination.
CRIS-Team WoS Importer:2022-03-04